Vegetation ecology of Central Europe. Volume I, - Leuschner, Christoph; Ellenberg, Heinz, 1913- (Springer, 2017)
This is a comprehensive handbook in two volumes covering the heart of the continent, including Germany, Poland, the Netherlands, Belgium, Luxembourg, Switzerland, Austria, Czech Republic and Slovakia. Based on a thorough literature review with 5500 cited references and illustrated with nearly 1000 informative figures and tables, all vegetation types of this region are analysed in terms of the climatic and edaphic influences, the structure and dynamics of their communities, the ecophysiological constitution of the main plant species, important aspects of ecosystem functioning, and recent conservation issues. This volume deals with forest and scrub vegetation, be it natural or man-made, whilst Volume II is dedicated to the open habitats containing non-forest vegetation such as mires, grasslands, heaths, alpine habitats and urban vegetation. Chapters 1 and 2 of this volume present the climatic, geological and pedological characteristics of Central Europe and provide a short introduction to its phytogeography. Chapter 3 gives a concise overview of the pervasive impact of man on the ecosystems and landscapes of this region over the last 7000 years, referring to both forests and non-forest vegetation. General aspects of the ecology of Central European tree species and forests are summarised in Chapter 4, which also contains a brief review of recent anthropogenic stressors of forest ecosystems, notably over-use, climate change, and the atmospheric deposition of nitrogen and strong acids. Chapters 5, 6 and 7 deal with the broadleaved and coniferous forest communities not shaped by flooding or high water tables. Forest plantations are the topic of Chapter 8, followed by floodplain and swamp forests (Chapter 9), forest epiphytic vegetation (Chapter 10), and the scrub vegetation of forest edges and hedges (Chapter 11). The summarising chapter (12) gives an overview of the most important plant communities of Central Europe.- Resumé vydavatel
Revised and extended version of the 6th German edition.
Keywords: ekologie lesa -- Evropa střední; forest ecology -- Europe, Central; elektronické knihy; monografie; electronic books; monographs